2002
DOI: 10.4049/jimmunol.168.8.4112
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 and 5-Lipoxygenase Products Recruit Leukocytes in Response to Platelet-Activating Factor-Like Lipids in Oxidized Low-Density Lipoprotein

Abstract: Oxidized low-density lipoprotein (LDL) contains inflammatory agents, including oxidatively fragmented phospholipids that activate the platelet-activating factor (PAF) receptor, but in vivo events caused by these pathologically generated agents are not well defined. Injection of PAF-like lipids derived from oxidized LDL, or C4-PAF that is a major PAF-like lipid in these particles, into the pleural cavity of mice resulted in rapid monocyte, neutrophil, and eosinophil accumulation. Increased numbers of intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 50 publications
1
61
0
Order By: Relevance
“…Indeed, stimuli known to prime leukocytes to induce eicosanoid generation, including PKC activators, arachidonate and PAF, are also active in stimulating lipid body formation. Accordingly, others and we observed a significant correlation between lipid body formation and enhanced generation of both LO-and COX- derived eicosanoids in vitro (Bozza et al 1996a, b, 1997, Bartmenes et al 1999 as well as in vivo , Silva et al 2002, de Assis et al 2003. Analogously, agents that inhibited lipid body formation also resulted in inhibited priming for eicosanoid production.…”
Section: Involvement Of Lipid Bodies In Enhanced Generationsupporting
confidence: 62%
See 3 more Smart Citations
“…Indeed, stimuli known to prime leukocytes to induce eicosanoid generation, including PKC activators, arachidonate and PAF, are also active in stimulating lipid body formation. Accordingly, others and we observed a significant correlation between lipid body formation and enhanced generation of both LO-and COX- derived eicosanoids in vitro (Bozza et al 1996a, b, 1997, Bartmenes et al 1999 as well as in vivo , Silva et al 2002, de Assis et al 2003. Analogously, agents that inhibited lipid body formation also resulted in inhibited priming for eicosanoid production.…”
Section: Involvement Of Lipid Bodies In Enhanced Generationsupporting
confidence: 62%
“…Although PAF may act at intracellular binding sites to induce cell activation (Bazan et al 1994), results are suggestive that PAF is acting in a paracrine/autocrine way to induce lipid body formation, since the PAF-receptor antagonist used in those studies would act preferentially at membrane receptors and confirmed by findings that LPS or oxLDL induced lipid body formation were inhibitable by treatment with extracellular PAH-acetylhidrolase (Silva et al 2002).…”
Section: Mechanisms Of Leukocyte Lipid Body Formationmentioning
confidence: 81%
See 2 more Smart Citations
“…[12][13][14] Both MCP1 and 5LO products recruit leukocytes to sites of inflammation. 15 These data indirectly suggest that ALOX5AP also might play a role in obesity.…”
Section: Introductionmentioning
confidence: 91%